Seismic isolation implemented for the structural block 1 in the new scientific research center ESPE University of Armed Forces (Ágora de Heterodoxias, 2015)
Universidad de Fuerzas Armadas ESPE planned the construction of the new Scientific Research and Posgrades Center. Eigth steel structural blocks were designed in the traditional way, without passive control systems.  Since this is a flag building inside the university and, taking into account the cost of the laboratories and hardware equipment, it was decided that some structural blocks will work with seismic isolators to limit the lateral displacements and accelerations. In this paper, the results are compared in the structural block 1 without isolators, the original design, and with isolators, the new proposed design. In this way, the seismic analysis theoretical frame is briefly presented for structures without and with isolators. The modal superposition method is employed for this purpose.
Keywords: seismic isolators; modal superposition method; seismic isolated structure